Novel paradigm for integrated photonics circuits : transient interconnection network - Fazio, Eugenio (2019)
Self-confined beams and spatial solitons were always investigated for a purely academic point of view, describing their formation and cross-interaction. We propose a novel paradigm for integrated photonics circuits based on self-confined interconnections. We consider that circuits are not designed since beginning; a network of writing lasers provide the circuit configuration inside which information at a different wavelength travels. we propose new designs for interconnections and both digital and analog switching gates somehow inspired by Nature, following analog decision routes used in biological networks like brain synapsis or animal path finding.